5. WEATHER RADAR SYSTEM FAILURE ANALYSIS ON AN AIRBUS 320-200 AIRCRAFT AT PT GMF AEROASIA USING FMEA AND RCA TO IMPROVE RELIABILITY AND SAFETY - Alfina Rahmawati; Bhima Shakti Arrafat; Muhamad Faridh Al Farisy; Muchammad Furqon; Muqdhatas; Tia Tsania (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the failure of the Weather Radar System using amixed-methods sequential explanatory approach. Flight safety is highly dependent on thereliability of avionics systems, one of which is the Weather Radar System that functions todetect extreme weather phenomena. Damage to this system is categorized as a no-go itemin the MEL and based on data from the Top Delay Report of PT GMF Aero Asia Tbk for theperiod 2020–2024, it ranks fifth as the highest cause of delays on the Airbus A320-200, with341 failure reports. The quantitative stage uses Failure Mode and Effects Analysis (FMEA)and Pareto Diagrams to identify critical components, while the qualitative stage uses RootCause Analysis (RCA) and Fishbone Diagrams to explore the root causes of failure. Theresults show that the Transceiver is the most problematic component with 39% ofunscheduled removals with the dominant failure mode being Intermittent Signal with an RPNvalue of 336. RCA reveals the main causal factors including human error, non-compliancewith procedures, limited tools, low material quality, and exposure to extreme environments.Recommendations for improvement include improving technician competency, toolprocurement and calibration, stringent material vendor selection, and system protection fromextreme weather. This research is expected to support increased maintenance effectiveness,reduce delays, and strengthen the safety culture at GMF.